Peningkatan Daya Ingat Anak Melalui Proses Menghafal Dan Menyanyi Suatu Mantra Bagi Siswa Kelas V SD di Pasraman Candra Prabha - Luh Yuniati (Pasupati, 2023)
The background of this scientific work is taken from the curiosity of the writer to know the effect of the learn results of students grade 5 primary school in Pasraman Candra Prabha Jelambar through the process of memorizing and singing thea spell. Teaching students to memorize a spell using the usual method of memorizing is very difficult to remember because students are easily feel bored. Therefore, by applying singing method in memorization a spell as a method of learning expected to improve the effectiveness remember students in memorization a spell. Based on it, formulation of the problem in this research is whether a method of singing can increase a memory of students in memorization a spell. Research aims to understand the increase in memory of students in memorization a spell. Design in this research using the kind of research the act of a class that requires the collaboration between practitioner and researchers in understanding agreement about the problems and the decision-making process finally delivery sameness of action. Therefore, in this research researchers conducted collaboration with teachers (homeroom). Variables used in this research is the variable free and output variable. Data collection techniques are done through observation, test, assessment and literature. Data analysis technique used in this research is quantitative analysis. This research result indicates that method singing can increase the remember students in memorization a spell. Based on the data the result of this research, the average class that uses the method memorization < method of singing in remembering a spell is 65 < 86, so that can be concluded that method sing in memorization a spell able to increase memory students. Students who formerly less excited in following learning became more motivated because singing is the funnest thing. Based on the outcome of this research, it is suggested that method of singing be able to apply in their learning in the pasraman or at school, because it is very suitable when there is a a learning process that require rote.